(untitled) (Baghdad Science Journal, 2013)
The chemical, physical and toxicological effects on health of synthetic dyes that used as tracking dye in the electrophoresis requires seriously search about alternative tracking dye. The present study is aimed to find an alternative dye from safe food dyes which commonly used in food coloring. Five dyes were selected depending on their chemical properties and the availability in local market: Brilliant Blue FCF, Tartrazine, Sunset Yellow FCF, Carmoisine, and green traditional, three dyes were chosen to be mixed as loading buffer: Brilliant Blue FCF, Sunset Yellow FCF as a basic because it give the whole range size of most traditional loading buffers that available in market, and adding the Carmoisine as a new indicator for the bands less than 50bp, then mixed with DNA ladder in same percentage used with traditional loading buffers to clarify the effects of dyes on DNA, migrated on 1% agarose with loading buffer promega, results showed more clarity and highly readable separation of dyes and give wide range of size in the food loading mix than promega loading dye, by viewing the gel on UV light the DNA ladder were moved smoothly, bands separated effeminately on gel and in same rate of the DNA ladder that load with promega loading buffer which indicate no interaction between the food dyes and the DNA.Our studies show that the food dye can be used as a tracking dye in place of used synthetic dye. The procedure is found to be easy, practical, safely and reliable.